Hearing, Holding, and Living the Word: Scripture as Divine Revelation for Discipleship Among Youth and Emerging Adults - JOEL ALABI (Fakultas Filsafat Universitas Advent Indonesia, 2026)
Youth and emerging adults live in a cultural context characterized by information overload, spiritual fragmentation, and declining biblical literacy. While access to Scripture has never been greater, its formative authority is increasingly challenged by digital media, expressive individualism, and moral relativism. This article examines the cultural and spiritual influences shaping identity formation among younger generations and argues for the recovery of Scripture as God’s authoritative self-revelation and the foundation of Christian discipleship. Using an integrative biblical-theological and practical-theological approach grounded in a canonical and Christocentric hermeneutic, the study explores divine revelation as God’s initiative, its fulfillment in Jesus Christ as the living Word, and Scripture’s continuing role in shaping believers through the work of the Holy Spirit. By connecting doctrinal theology with practical discipleship, the article proposes a theologically robust and pastorally relevant framework for cultivating resilient, Christ-centered, and Word-shaped Christian identity amid the challenges of contemporary culture.